Analisis bahasa sufistik dalam Kitab Sirr Al-Asrār karya As-Syeikh Abdul Qadir Al-Jailani - Hidayat, Dudung Rahmat (citeus, 2016)
This study emphasizes on the use of language in the Sufi book entitled Sirr al-Asrar wrriten by Sheikh Abdul Qadir al-Jilani. The purpose of this study is to analyze the content and the language used and the implications for learning Musykilat Ta'lim Al-lughah Al-'Arabiyah. The method used in the study is the Research and Development (R & D) which includes three main activities; they are: (1) an analysis of the contents of the form language of Sufi books Sirr al-Asrar, (2) the conceptualization of teaching materials Sufism language, (3) a trial or usur application Sufi language courses against Musykilat Ta'lim al-lughah al-'Arabiyah Lighair Nāṭiqīna Biha in Arabic Education Graduate Program UPI. The method of this study is qualitative description by employing Sirr al-Asrar as a data source. The results showed that there are some meaningful expressions in the form of words or phrases with symbolic, figurative and metaphorical. There are 1064 Sufi vocabulary and meaning of language and some Sufi terms and their meanings.